Virulence spectrum of Erysiphe graminis f.sp. tritici in Himachal Pradesh - and PD. TYAGI, RAX PAUL, ASHWANI K. BASANDRAI (Indian Phytopathology, 2002)
Virulence spectrum of 45 conidial and 11 ascosporic single colony isolates collected from different agroclimatic zones of Himachal Pradesh was typed on the basis of their reaction on different wheat lines having genes Pm1 to Pm8, Pm(Ma) and combinations of genes Pm2 + Pm4b, Pm4b + Pm8 and Pm2 + Pm6. The isolates were grouped into 29 virulence combinations (pathotypes). Pathotypes with intermediate virulence (on 3-6 genes) were more frequent. Virulence combination Pm1, Pm2, Pm4a, Pm2 + Pm6, Pm2 + Pm4b, Pm4b + Pm8/Pm3a, Pm3b, Pm3c, Pm5, Pm6, Pm8, Pm(Ma) was the most virulent and virulence combination Pm1, Pm2, Pm3a, Pm3b, Pm3c, Pm4a, Pm5, Pm6, Pm7, Pm8, Pm2 + Pm6, Pm2 + Pm4b, Pm4b + Pm8/Pm(Ma) was the least virulent. The latter virulence alongwith virulence combination Pm1, Pm2, Pm3b, Pm4a, Pm2 + Pm6, Pm2 + Pm4b, Pm4b + Pm8/Pm3a, Pm3c, Pm5, Pm6, Pm7, Pm8, Pm(Ma) were the most prevalent. Genes Pm2, Pm4a, Pm2 + Pm4b and Pm4b + Pm8 were effective against all the pathotypes of E. graminis f.sp. triticiin the state. Virulence was rare on genes Pm1 and Pm2 + Pm6.